A pilot programme of clinical practice improvement for future consultant doctors. (3rd May 2016) - Oates, Kim; Vinters, Cathy; Cass‐Verco, John; Fletcher, Mandy; Kaur, Narinder; Mherekumombe, Martha; Tang, Alice
Summary: Background: To provide junior doctors with tools to improve patient care in their workplace, a partnership was developed between the Clinical Excellence Commission (CEC) and the Royal Australasian College of Physicians (RACP) to help trainee consultants carry out clinical practice improvement (CPI) projects during clinical work. Methods: Based on a patient‐care problem they wished to resolve, trainee consultants attended a 2–day face‐to‐face workshop to learn quality‐improvement methods, describe their proposals and refine them using CPI methodology. They were provided with continuing supervision, participated in a mid‐point review and were responsible for driving their projects. Trainee consultants attended a 2–day face‐to‐face workshop to learn quality‐improvement methods Results: Examples of five projects are: reducing mislabelled specimens leaving an emergency department, from 82 in the baseline period to 18 following the intervention; creating a multidisciplinary team to reduce hypoglycaemic episodes on a diabetic ward, from 23 episodes at baseline to three episodes over the same time period after the intervention; establishing an acute paediatric review clinic that reduced avoidable admissions of pneumonia by 74 per cent; providing 100 per cent of patients in a palliative care unit with an effective pain‐management plan; developing an education package to increase staff confidence in recognising and responding to anaphylaxis in children, producing an increase in confidence from 51 per cent at baseline to 100 per cent after the intervention. Discussion: Involving a learned college such as the RACP in patient‐care improvement, with educational input from a partner organisation, shows how junior staff can become effective leaders in improving patient care.